1995
DOI: 10.1080/14640749508401404
|View full text |Cite
|
Sign up to set email alerts
|

Priming Production of People's Names

Abstract: Surnames of celebrities that are English words (e.g. “Wood”, “Bush”, “Sleep”) were used to explore the relationship between production of common names and proper names that share the same phonology. No effect of priming of face naming latency was found from a prime task in which a written common name was presented and was read aloud, even when subjects were informed the words that they would read aloud were surnames. Production of common names to complete a sentence did not prime famous-face naming. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
3
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
7
32
3
1
Order By: Relevance
“…The role of contextual features in proper noun processing has been investigated from many points of view (e.g., Seamon & Travis, 1993; for review see Valentine, Brennen, & Brédart, 1996). Our notion is similar to that expressed by Valentine, Moore, and Bredart (1995): In an information processing model, the personally relevant meanings might be said to add weight onto the linkage from person identity to the output lexicon. Our view is also compatible with the ideas of Burgess and Conley (1999) about semantic neighborhoods, which consist of other words related in meaning to the target word; they state that ''neighborhoods for famous PNs (proper nouns) [e.g., Reagan] are quite different'' from lexical neighborhoods for unfamiliar PNs (e.g., John).…”
Section: Resultsmentioning
confidence: 96%
“…The role of contextual features in proper noun processing has been investigated from many points of view (e.g., Seamon & Travis, 1993; for review see Valentine, Brennen, & Brédart, 1996). Our notion is similar to that expressed by Valentine, Moore, and Bredart (1995): In an information processing model, the personally relevant meanings might be said to add weight onto the linkage from person identity to the output lexicon. Our view is also compatible with the ideas of Burgess and Conley (1999) about semantic neighborhoods, which consist of other words related in meaning to the target word; they state that ''neighborhoods for famous PNs (proper nouns) [e.g., Reagan] are quite different'' from lexical neighborhoods for unfamiliar PNs (e.g., John).…”
Section: Resultsmentioning
confidence: 96%
“…Prior exposure to a face acts to reduce reaction times in tasks such as face naming (Valentine, Moore, & Bredart, 1995), familiarity judgments (Bruce & Valentine, 1985), and semantic classification (A. W. Ellis, Young, Flude, & Hay, 1987;Lewis & H. D. Ellis, 1999). The repetition-priming effect can be long lasting and is largest when exactly the same view of the primed individual is shown .…”
Section: Priming Effectsmentioning
confidence: 99%
“…The mechanism responsible for a priming effect, were it to be observed, is a relatively long-term change in connection strength, which is the mechanism of interest in the present research (MacKay, 1987;Valentine et al, 1995;Wheeldon & Monsell, 1992). In contrast, researchers using a very brief prime-to-target-generation interval of a few hundred milliseconds reported that phonologically related prime words facilitated picture naming, and they attributed this to a different mechanism: a very short-lived residual priming in nodes that are common to the prime and target or that spread from prime to target (Collins & Ellis, 1992;McEvoy, 1988;Schriefers, Meyer, & Levelt, 1990).…”
mentioning
confidence: 99%